2023
DOI: 10.1080/07853890.2023.2169343
|View full text |Cite
|
Sign up to set email alerts
|

Emergency decompression for patients with ureteral stones and SIRS: a prospective randomized clinical study

Abstract: Objective Patients with ureteral calculi and systemic inflammatory response syndrome (SIRS) often require emergency drainage, and percutaneous nephrostomy (PCN) and retrograde ureteral stent insertion (RUSI) are the most commonly used methods. Our study aimed to identify the best choice (PCN or RUSI) for these patients and to examine the risk factors for progression to urosepsis after decompression. Methods A prospective, randomized clinical study was performed at our h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…The management of UROP is warranted by urgent decompression, which can be achieved either by PCN or ureteral stent placement, thereby decreasing complications in high-risk patients [30]. One meta-analysis showed no significant difference between the two methods regarding the improvement of septic parameters, quality of life, failure rates, or post-procedural pain [31].…”
Section: Discussionmentioning
confidence: 99%
“…The management of UROP is warranted by urgent decompression, which can be achieved either by PCN or ureteral stent placement, thereby decreasing complications in high-risk patients [30]. One meta-analysis showed no significant difference between the two methods regarding the improvement of septic parameters, quality of life, failure rates, or post-procedural pain [31].…”
Section: Discussionmentioning
confidence: 99%
“…While this interval is sufficient for majority of patients, previous studies have shown that there is an increasing incidence of Emergency Department visits for acute PCN exchanges, resulting in increased economic burdens on these patients and the health system. 10…”
Section: Introductionmentioning
confidence: 99%